2006
DOI: 10.1111/j.1574-6968.2006.00244.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the attachment of rhizospheric bacteria to bean and soybean roots

Abstract: The plant rhizosphere is an important soil ecological environment for plant-microorganism interactions, which include colonization by a variety of microorganisms in and around the roots that may result in symbiotic, endophytic, associative, or parasitic relationships within the plant, depending on the type of microorganisms, soil nutrient status, and soil environment. Rhizosphere competence may be attributable to the differences in the extent of bacterial attachment to the root surface. We present results of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(53 citation statements)
references
References 30 publications
2
48
0
3
Order By: Relevance
“…Within the nodule, bacteria differentiate to bacteroids that fix atmospheric nitrogen (10). Several factors, including pH, ionic strength, bacterial motility, and chemotaxis, as well as the synthesis of the extracellular acidic exopolysaccharide (EPS) were proposed to influence rhizobial attachment to root hairs (11,12). Results of several studies indicate that EPS may also affect root invasion and nodule development (8,13).…”
mentioning
confidence: 99%
“…Within the nodule, bacteria differentiate to bacteroids that fix atmospheric nitrogen (10). Several factors, including pH, ionic strength, bacterial motility, and chemotaxis, as well as the synthesis of the extracellular acidic exopolysaccharide (EPS) were proposed to influence rhizobial attachment to root hairs (11,12). Results of several studies indicate that EPS may also affect root invasion and nodule development (8,13).…”
mentioning
confidence: 99%
“…En este estudio, la estructura y abundancia de las bacterias aisladas puede asociarse con la interacción de varios factores, incluyendo el genotipo de la planta, las características genéticas de la bacteria, el suelo, la temperatura, ciclo de cultivo y fenología de la planta de maíz (Li et al, 2014;Oliveira et al, 2009) que influyen en la colonización y dinámica de las comunidades bacterianas endófitas (Bodenhausen et al, 2013). Se ha mostrado la relación específica entre planta-endófito mediante una quimiotaxia bacteriana hacia exudados de la planta hospedante como fuentes de carbono que actúan como moléculas de señalización (Albareda et al, 2006) y que las diferencias en la composición y patrones de exudación son dependientes del cultivar, etapa de desarrollo, exposición a estrés de la planta y tipo de suelo, los cuales influencian la colonización por comunidades bacterianas (Haichar et al, 2008). Estudios en maíz indicaron que los exudados de la raíz están compuestos de 65% de azúcares, 33% de ácidos orgánicos y 2% de aminoácidos y que los cambios en cantidad y calidad en estos patrones de exudación en las diferentes etapas del crecimiento y fisiología de la raíz, influyó en la biomasa y estructura de las comunidades bacterianas incrementando la actividad y deposición de nutrientes por estas comunidades microbianas beneficiando el crecimiento de la planta (Baudoin et al, 2003).…”
Section: Resultados Y Discusiónunclassified
“…In this study, the structure and large number of isolated bacteria may be associated with the interaction of several factors, including plant genotype, the genetic characteristics of bacterium, soil, temperature, crop cycle and maize plant phenology (Li et al, 2014;Oliveira et al, 2009) that influence the colonization and dynamics of the endophytic bacterial community (Bodenhausen et al, 2013). A specific plant-endophyte relationship was revealed by performing bacterial chemotaxis on host plant exudates as carbon sources that act as signaling molecules (Albareda et al, 2006); it also showed that differences in exudate composition and patterns depend on the crop variety, development stage, exposure of the plant to stress and type of soil, which influence colonization by bacterial La estructura taxonómica y funcional de las comunidades bacterianas en el suelo está influenciada por factores bióticos y abióticos como las caracterís-ticas físicoquímicas del suelo, condiciones climáticas, communities (Haichar et al, 2008). Studies on maize indicated that root exudates are 65% sugar, 33% organic acids and 2% amino acids, and that changes in the quantity and quality of exudation patterns at different root growth and physiological stages influenced the biomass and the structure of bacterial communities by increasing nutrient activity and deposition by those microbial communities and favored plant growth (Baudoin et al, 2003).…”
mentioning
confidence: 99%
“…The plant rhizosphere is an essential soil ecological environment for plant-microorganism interactions, which include colonization by a variety of microorganisms in and around the roots that may result in symbiotic, endophytic, associative, or parasitic relationships within the plant, depending on the type of microorganisms, soil nutrient status, and soil environment (Albareda et al 2006). In this sphere, intensive interactions are taking place between the plant, soil, soil microfauna and microorganisms, where bacteria are the most abundant microorganisms (Antoun and Kloepper, 2001).…”
Section: Plant Growth-promoting Rhizobacteriamentioning
confidence: 99%